Navigating the Digital Transformation: Unveiling the Role of Business Administration in Museums' Evolution - Marko Ljubič (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
The digital transition of museums and cultural heritage institutions has gained momentum with the increasing demand for digital experiences, especially against the COVID-19 pandemic. This paper explores the existence and development of business models for museum operations in the digital age. While digitising contents and objects is evident, the digitalisation of museum business activities and management remains underexplored. This study reviews relevant literature to analyse the role of business administration in the digital transformation of museums. Key themes, including the integration of digital technologies, business model innovation, organisation transformation, and challenges posed by the pandemic. Through a comprehensive literature review, this paper emphasises the importance of holistic approaches and adaptive strategies in navigating the complexities of digital transformation in the museum sector. Museum business administration should be essential in ensuring digital technologies are integrated seamlessly into the museum's operations and workflows. While there is a growing body of research on business models for museums and cultural heritage institutions in the digital age, there are still some limitations and gaps in the existing literature.
Keywords: M10; O30; 330; digital transformation; museum business model; cultural heritage; digital technologies; museum administration